ANALISIS PENGARUH KINERJA KEUANGAN DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Hanggi Arinda; Susi dwimulyani (Jurnal Akuntansi Trisakti, 2018)
The purpose of this study was to examine the influence of profitability, leverage, sales growth, and audit quality to tax avoidance moderated good corporate governance. The population in this study is the registered manufacturing companies in Indonesia Stock Exchange in 2011 until 2017.  Election samples by purposive sampling method . The data used in this research is a secondary data obtained from www.idx.co.id. Data collection techniques with technique of documentation. Data were analyzed using multiple regression analysis with SPSS. Based on the analysis, it can be concluded that profitability positively affect tax avoidance and leverage negatively affect to tax avoidance. Good corporate governance can only weaken the positively effect of the profitability to tax avoidance.